Elastic Properties of α- and β-phases of Li3N - Hossain, M. A.; Islam, A.K.M. A; Islam, F. N. (Journal of Scientific Research, 2009)
Investigations of elastic properties of Li3N in both α- and β-phases have been made by first-principles methods (HF-LCAO, DFT as implemented in CRYSTAL98 and in CASTEP). The theoretical equation of state of the α-phase (D46h structure) produced by our total-energy calculations is compared with the experimental EOS. Five independent elastic constants are calculated for the first time for both the phases. These are compared with the available four elastic constants of α-Li3N estimated from the slopes of the acoustic branches in the long wavelength region of the measured phonon dispersion curves. The aggregate elastic moduli (B, G, E), the Poisson’s ratio (ν) and the Debye temperature ΘD as a function of pressure are also calculated and the results discussed. Keywords: Li3N; α- and β-phases; Elastic properties; Debye temperature. ©?2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1763